2020
DOI: 10.21203/rs.2.21718/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Age-dependent involvement of gut mast cells and histamine in post-stroke inflammation

Abstract: Background Risk of stroke-related morbidity and mortality increases significantly with age. Aging is associated with chronic, low-grade inflammation, which is thought to contribute to the poorer outcomes after stroke seen in the elderly. Histamine (HA) is a major molecular mediator of inflammation and mast cells residing in the gut are a primary source of histamine. Methods Stroke was induced in male C57BL/6J mice at 3 months (young) and 20 months (aged) of age. Role of histamine after stroke was examined usin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 64 publications
(120 reference statements)
0
4
0
Order By: Relevance
“…However, a recent study in aged mice following experimental stroke showed that stroke resulted in increased intestinal mast cell numbers and intestinal histamine receptor expression levels. In the peripheral circulation, these gut-centered changes were linked to increased histamine levels and other proinflammatory cytokines (such as IL-6, TNF-α, and IFN-γ) [71]. It is obvious that histamine mediates host-microbe crosstalk as a neuroimmune system; however, it is still unclear how host histamine may affect microbial activity.…”
Section: Immunementioning
confidence: 99%
See 1 more Smart Citation
“…However, a recent study in aged mice following experimental stroke showed that stroke resulted in increased intestinal mast cell numbers and intestinal histamine receptor expression levels. In the peripheral circulation, these gut-centered changes were linked to increased histamine levels and other proinflammatory cytokines (such as IL-6, TNF-α, and IFN-γ) [71]. It is obvious that histamine mediates host-microbe crosstalk as a neuroimmune system; however, it is still unclear how host histamine may affect microbial activity.…”
Section: Immunementioning
confidence: 99%
“…Recent research using experimental animal models has revealed that older mice tend to be more susceptible to infection after IS, which is at least partially caused by decreased intestinal barrier integrity and intestinal inflammation, as well as reduced expression of mucin and tight-junction proteins, which facilitates bacterial translocation [71]. Aged mice had a worse prognosis after IS than young mice.…”
Section: Gut Dysbiosis and Is Risk Factorsmentioning
confidence: 99%
“…In the CNS, the neuroactive metabolites histamine and tryptophan play a crucial role in neuroprotection against neuroinflammation in SOD1 G93A mice 31,32 and mediates inflammation in the PNS via production of mast cells in the gut 33 and producing commensal gut microorganisms via microbial decarboxylation of amino acids 34 . Thus, we observed changes in histamine, tryptophan and glutamate related amino acids.…”
Section: Neuroactive Metabolites Increase Significantly At Onset In A...mentioning
confidence: 99%
“…CRH also increased intestinal permeability in humans [211] via stimulation of mast cells by CRH. In fact, gut mast cells are now invoked in the pathogenesis of brain injury [212,213] and as a therapeutic target for neurodegenerative diseases [208,214].…”
Section: N O V Amentioning
confidence: 99%